Process selection, modelling and optimization of a water scrubbing process for energy-self-sufficient biogas upgrading plants. (June 2018) - Magli, Francesco; Capra, Federico; Gatti, Manuele; Martelli, Emanuele
Abstract: This study focuses on the techno-economic optimization of an energy-self-sufficient biomethane production plant based on anaerobic digestion of agricultural residues and maize silage and an optimized water scrubbing process. The biomethane production plant features a biogas production system, a water scrubbing upgrading section and an internal combustion engine fed with a fraction of the produced biogas. The engine is properly sized to provide both the electric and thermal power required to operate the whole plant. A thorough literature review is performed to select the most promising water scrubbing layout, which features a scrubber, a flash and a stripping column. Accurate process and preliminary cost models of the main equipment units are developed and validated against literature and industrial data. A techno-economic bi-objective optimization of the upgrading process is then performed in order to determine the set of Pareto optimal solutions with maximum net biomethane recovery efficiency and minimum capital cost. Process optimization is performed with a black-box strategy using the PGS-COM single-objective algorithm and the NSGA-II multi-objective algorithm. The resulting Pareto front achieves net biomethane recovery figures in the range 88.1–89.7% and specific Total Equipment Costs between 0.95 and 1.03 k€/(Nm 3 BM /h). Compared to the conventional plant configuration, the proposed integration allows to avoid 188 g CO2 /Nm 3 BM emissions and to save between 6.8 and 8.5% of primary energy, with an estimated increase of Total Equipment Cost of approximately 11–13.5% (anaerobic digestion section included).